Formigas como modelo - uma abordagem ecológica e artística - Nascimento, Gabriela Bandeira do (2021)
Models, in mathematics and statistics, can be simpler representations of reality that help us understand existing relationships in nature, while in the field of art it can be an object that is part of the creative process or part of the integral manifestation of a technique. Regardless of the definitions in the different fields, it is the goal of this dissertation to demonstrate that ants can be used as model organisms and drive research in different fields. To this end, the dissertation was constructed in two chapters with distinct objectives: (1) To advance information about the geographical distribution patterns of Camponotus (Dendromyrmex) and predict possible locations of occurrence through a potential distribution modeling; (2) to know and understand the relationship that humans have with ants through the survey of artistic manifestations created over the years, regardless of the location. As methodology in the first chapter, we gathered data on occurrence through articles and entomological collections and used five different algorithms and 19 variables to construct the environmental pattern. We found that the distribution pattern of Camponotus (Dendromyrmex) is Neotropical, with a potential expansion of the current distribution. In the second chapter we developed three approaches for data collection (web page, virtual access to museum collections, and Google Arts&Culture platform). As a result we found 50 artistic manifestations distributed in various types and styles over time. The works are distributed in the American, Asian and, mainly, European continents. These chapters are important steps towards the understanding of ants as an ecological model, as knowledge is advanced in relation to Camponotus (Dendromyrmex), but also around the relationship that humans have established and expressed about ants over the years, contributing to the knowledge about ants in the socio-cultural and artistic field.